2009
DOI: 10.1080/15568310802260013
|View full text |Cite
|
Sign up to set email alerts
|

Relieving Congestion by Adding Road Capacity and Tolling

Abstract: Congestion is already severe and projected to worsen in U.S. metro areas. Few current long-range transportation plans call for reducing congestion. Yet the costs congestion imposes make reducing it imperative. Capacity additions are a key part of reducing congestion. We estimate nationwide capacity needs to keep volume=capacity below 1.0 and thus avoid severe congestion over the next 25 years and the costs of building the new capacity. We then examine a set of specific capacity additions in Atlanta and establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Increases in road density and traffic volumes are typical features associated with greater urbanisation and human population growth, and are therefore fundamental considerations in conserving biodiversity [62] . A key planning decision that needs to be made for reducing the impact of roads on wildlife is whether we should accommodate increased traffic loads by increasing traffic on existing roads, by increasing the density of roads, or through a combination of both [63] . We have shown that, by using a simple model of animal movement and road mortality, key insights can be gained about the relative impacts of increases in road density versus increases in traffic volume on existing roads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in road density and traffic volumes are typical features associated with greater urbanisation and human population growth, and are therefore fundamental considerations in conserving biodiversity [62] . A key planning decision that needs to be made for reducing the impact of roads on wildlife is whether we should accommodate increased traffic loads by increasing traffic on existing roads, by increasing the density of roads, or through a combination of both [63] . We have shown that, by using a simple model of animal movement and road mortality, key insights can be gained about the relative impacts of increases in road density versus increases in traffic volume on existing roads.…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of cases, we found that increasing road density elevated mortality rates more rapidly than did increasing traffic volume on existing roads. Decisions about where and how to build additional road capacity are governed by a range of factors, such as the spatial distribution of capacity requirements and implications for congestion [63] . However, our study indicates that strategies that focus on the creation of new roads are likely to be more harmful to wildlife than those that build capacity within an existing network.…”
Section: Discussionmentioning
confidence: 99%
“…ough it does not necessarily hold true for each individual road development project, it is commonly referred to in the transport planning literature to point out that urban road capacity expansion projects often do not bring the desirable user benefits-i.e., they do not speed up the car journeys, smoothen out the traffic flow, relieve traffic jams, etc. as expected-as in longer run they will attract additional flows [22]. Notably, the traffic induction is not only related to the road network itself but also to parking policy [23], road pricing policy, and land use [24].…”
Section: Introductionmentioning
confidence: 59%
“…The impact of congestion also causes huge losses for road users, especially in terms of wasting fuel (Susanti, 2015), wasting time and convenience (Tamin, 2008). In a study by Fields et al, (2009) stated that community productivity will be low if they spend more time stuck in traffic jams, and according to Rahane & Saharkar in C Jalagat & M Jalagat, (2016), community productivity is low due to increased stress levels on the road. highway.…”
Section: Traffic Congestionmentioning
confidence: 99%